2004
DOI: 10.1242/jcs.00836
|View full text |Cite
|
Sign up to set email alerts
|

Cell behaviour on micropatterned substrata: limits of extracellular matrix geometry for spreading and adhesion

Abstract: Cell adhesion, spreading and migration require the dynamic formation and dispersal of contacts with the extracellular matrix (ECM). In vivo, the number, availability and distribution of ECM binding sites dictate the shape of a cell and determine its mobility. To analyse the geometrical limits of ECM binding sites required for cell attachment and spreading, we used microcontact printing to produce regular patterns of ECM protein dots of defined size separated by nonadhesive regions. Cells cultured on these subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
326
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(334 citation statements)
references
References 47 publications
7
326
0
1
Order By: Relevance
“…On the other hand, actin-stained images of cells contracting under micro-patterned constraints or micro-needles placed at the corners of square and triangular geometries show distinct actin bundles or stress fibers forming at the edges of the geometry instead of diagonal. 39,51,74 …”
Section: Stress Fiber Patterns From Continuum Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, actin-stained images of cells contracting under micro-patterned constraints or micro-needles placed at the corners of square and triangular geometries show distinct actin bundles or stress fibers forming at the edges of the geometry instead of diagonal. 39,51,74 …”
Section: Stress Fiber Patterns From Continuum Modelsmentioning
confidence: 99%
“…It can be argued that the actin staining along the edges of contracting cells 39,51,74 is due to the cortical actin network and not stress fibers. However, the existence of edge or peripheral stress fibers in fibroblasts on rigid surfaces have been documented.…”
Section: Peripheral Stress Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that when cells are organized into square shapes with asymmetric adhesive patterns, cells polarize their mitotic axis in a specific direction based on the matrix pattern [21], suggesting that spindle orientation is largely dependent on spatial distribution of ECM ( Figure 3B). Using subcellular, adhesion-sized ECM islands, investigators have also revealed that controlling adhesion size, shape and density can itself feed back to control the degree of cell spreading and shape ( Figure 3C) [22]. Thus there are multiple scales at which one can use patterning to control cell function.…”
Section: Cell Shape Modulates Signals From the Ecmmentioning
confidence: 99%
“…Custom protein distributions created by microcontact printing (lCP) (Chen et al, 1997;Singhvi et al, 1994) have been shown to be useful for studying the mechanisms of cell signaling, adhesion, migration, and neurite outgrowth (Lehnert et al, 2004;Thomas et al, 2002). In lCP, these stamps are first ''inked'' with a solution of molecules (often proteins or thiols), and then brought into contact with a substrate.…”
Section: Introductionmentioning
confidence: 99%